State of the Art: Authenticity and Influencer Marketing - Afef, Sahli (International Review of Management and Marketing, 2024)
Digital marketing is a new form of marketing that uses several digital media to spread a message. Influencer marketing is a promising acquisition channel for companies to explore. Engaging with influencers can help a company improve its brand image and stand out in an increasingly competitive marketplace. However, these opinion leaders can influence the purchasing behavior of the target audience. These are individuals with skills in a particular field, using them to create quality content, they are recognized as experts in their field. The content they publish is often in the form of a personalized story incorporating their opinion on a situation, a product or a service. Success lies in establishing a genuine, preferably long-term, relationship between the brand and its influencers. The objective is to rigorously analyze the links and elements that give meaning to this “Influencer marketing authenticity” interaction. As part of this research, we presented a detailed literature review of authenticity and influence marketing.